Degradation of Proteins From Colostrum and Mature Milk From Chinese Mothers Using an in vitro Infant Digestion Model - Elwakiel, Mohèb; Boeren, Sjef; Wang, Wendan; Schols, Henk A.; Hettinga, Kasper A. (Frontiers in Nutrition, 2020)
This study provided insights into the degradation of human milk proteins in an in vitro infant digestion model by comparing colostrum (week 1) and mature milk (week 4) of 7 Chinese mothers individually. In this study, we adapted the exiting INFOGEST in vitro model, to conditions representative to infants (0 to 3-month-old). The level of undigested proteins was analyzed by LC-MS/MS after gel-electrophoretic separation and in-gel digestion. The BCA protein assay showed that the total undigested milk protein content decreased from the start to the end of digestion with variations between mothers, especially in the gastric phase (25–80%). Undigested proteins could also still be found after the intestinal phase, ranging from 0.5% to 4.2% of initial protein content. Based on LC-MS/MS analysis, milk protein digestion varied between the mothers individually, especially during the gastric phase. No differences could be observed between protein digestion from colostrum and mature milk after the intestinal phase. The highest levels of proteins remaining after intestinal digestion can be linked to the group immune-active proteins, for all mothers. The level of protease inhibitors and total protein content in the milk did not correlate with the overall proteolysis during digestion. The results also showed that milk serum proteins partly remained after the gastric phase, with 33% remaining from colostrum and 37% remaining from mature milk. More than 40 milk serum proteins were detected after the intestinal phase. Some of the highly abundant milk serum proteins (lactoferrin, serum albumin, bile salt-activated lipase, immunoglobulins, 1-antichymotrypsin) were still partially present intact after the intestinal phase, for all mothers. Caseins were also not completely digested in the gastric phase, with 35% remaining from colostrum and 13% remaining from mature milk. Caseins, on the other hand, were almost completely digested after the intestinal phase. The complete degradation of caseins into peptides might be related to their structural features. Overall, this study showed that digestion differed for the various human milk proteins by adapting an in vitro digestion model to infant physiological conditions, with the main differences between digestion of the milk from individual mothers being observed after gastric digestion.